Identification and characterisation of surface layers on Propionibacterium jensenii and P. freudenreichii subspecies shermanii - Van Schalkwyk, Corne (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1999.